Economic evaluation of temsirolimus on the basis of the results of the ARCC (Advanced Renal-Cell Carcinoma) study - de Portu, Simona; Carteni, Giacomo; Belisari, Andrea (Farmeconomia. Health economics and therapeutic pathways, 2009)
Introduction: metastatic renal cell carcinoma (mRCC) is highly resistant to chemotherapeutics, rendering limited antitumor effect. Temsirolimus, a specific inhibitor of the mammalian target of rapamycin kinase, may benefit patients with this disease. The Global ARCC Trial (Temsirolimus, Interferon Alfa, or Both for Advanced Renal-Cell Carcinoma) compared temsirolimus alone or temsirolimus plus interferon alfa with interferon alfa alone in mRCC. It has demonstrated that, as compared with interferon alfa, temsirolimus improved overall survival among patients with metastatic renal-cell carcinoma and a poor prognosis while the addition of temsirolimus to interferon did not improve survival. Aim: the objective of our study was to investigate the pharmacoeconomic impact in the Italian context of temsirolimus vs interferon alfa in patients with metastatic renal-cell carcinoma and a poor prognosis. Methods: economic evaluation is based on clinical outcome data from the ARCC trial and was carried out conducting a cost/effectiveness analysis, comparing economic and clinical consequences of temsirolimus (25 mg weekly) vs interferon alfa (18 MU 3 times weekly) in the perspective of the Italian National Health Service. Direct medical costs included in the analysis were drug costs, costs associated with the management of treatment-related serious adverse events (grade 3 and 4), cost related to progression and best supportive care. Effects were measured in terms of overall survival. A sensitivity analysis was performed. Results: the cost of temsirolimus or interferon alfa therapy amounted to approximately € 14,000 and € 2,000 patient respectively. The cost of hospitalization related to drug toxicity was about € 1,500 for temsirolimus and € 2,100 for interferon alfa. Temsirolimus shows an incremental cost per patient per month saved of € 3,767. Sensitivity analysis demonstrates that cost consequences parameters are sensitive to fluctuation. Discussion: this study is the first economic evaluation of ARCC trial based on the Italian context. This evaluation found that temsirolimus therapy in patients with metastatic renal-cell carcinoma and a poor prognosis is cost-effective.